INVESTIGATING THE APPLICATION OF BIOPHILIC DESIGN PRINCIPLES IN THE TRADITIONAL POL HOUSES OF AHMEDABAD WITH A CASE STUDY ON MANGALDAS NI HAVELI - Sheth, Chaitali; Pandey, Suman; Sinha, Anil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
" This paper examines the application of biophilic design principles within the traditional "Pol" houses of Ahmedabad, with a focused case study on Mangaldas ni Haveli. Biophilia, a term popularized by Edward O. Wilson in 1984, suggests that humans have an inherent desire to connect with nature, a concept now essential in sustainable design. While biophilic design often incorporates elements like plants, water, natural light, and ventilation to create a stronger human-nature connection, traditional architecture in India, particularly in Pol houses, naturally integrates similar principles. Ahmedabad’s designation as a UNESCO World Heritage City in 2017 emphasizes its rich architectural and cultural heritage, with Pol houses serving as enduring symbols of community, sustainability, and environmental adaptation. Mangaldas ni Haveli, a significant example of this architectural legacy, was evaluated for its biophilic elements using the 15 biophilic design patterns by Stephen Kellert and Elizabeth Calabrese. The study identifies 12 patterns, including natural materials, indirect experiences of nature, and spatial configurations that evoke a connection to the environment. Despite being situated in a dense urban context, Mangaldas ni Haveli effectively promotes well-being and offers a sustainable model for heritage conservation. This research highlights how integrating biophilic design into heritage conservation can preserve cultural and architectural significance while making these spaces relevant for modern needs. The findings underscore the potential for traditional architecture to inspire sustainable urban design, reinforcing the enduring value of biophilic principles in enhancing quality of life in urban areas.".